Characterization of Air Dissolution and Reappearance Under Pressure in Cement Pastes by Means of Rheology - Gálvez-Moreno, Daniel; Feys, Dimitri; Riding, Kyle (Frontiers in Materials, 2019)
Concrete pumping is the most used technique to transfer concrete from the mixer truck to the formwork. Numerous studies have been performed on the flow behavior of concrete in pipes, as well as the consequences of pumping on fluid and hardened concrete properties. One of the negative consequences of pumping concrete is a decrease in freeze-thaw resistance. This is caused by a decrease in air content and an increase in air bubble size, due to dissolution and reappearance of air and air bubble coalescence under pressure. This paper investigates the capability of rheology to understand air dissolution and reappearance in cement paste under combined action of pressure and flow. A majority of the air bubbles in the cement pastes show low capillary-numbers, indicating the applied stress is insufficient to overcome the surface tension. Removing air causes a decrease in viscosity (or shear stress), up to a certain threshold pressure sufficient for full dissolution of the air. For mixtures with small air bubbles, the sudden application of pressure causes an immediate decrease in viscosity or shear stress. Mixtures with larger bubbles display a more gradual decrease in viscosity with the application of pressure. At depressurization, the viscosity of the sample is recovered almost instantly, although in some cases the viscosity is not fully recovered. This can be attributed to either an immediate air loss or to a coarsening of the air-void system, resulting in less non-deformable air bubbles in the paste.